IGZO/WO3−x‐Heterostructured Artificial Optoelectronic Synaptic Devices Mimicking Image Segmentation and Motion Capture - Wu, Tong; Gao, Song; Li, Yang (Small (Weinheim an der Bergstrasse, Germany), 2024)
Currently, artificial neural networks (ANNs) based on memristors are limited to recognizing static images of objects when simulating human visual system, preventing them from performing high‐dimensional information perception, and achieving more complex biomimetic functions is subject to certain limitations. In this work, indium gallium zinc oxide (IGZO)/tungsten oxide (WO3−x)‐heterostructured artificial optoelectronic synaptic devices mimicking image segmentation and motion capture exhibiting high‐performance optoelectronic synaptic responses are proposed and demonstrated. Upon electrical and optical stimulations, the device shows a variety of fundamental and advanced electrical and optical synaptic plasticity. Most importantly, outstanding and repeatable linear synaptic weight changes are attained by the developed memristor. By taking advantage of the notable linear synaptic weight changes, ANNs have been constructed and successfully utilized to demonstrate two applications in the field of computer vision, including image segmentation and object tracking. The accuracy attained by the memristor‐based ANNs is similar to that of the computer algorithms, while its power has been significantly reduced by 105 orders of magnitude. With successful emulations of the human brain reactions when observing objects, the demonstrated memristor and related ANNs can be effectively utilized in constructing artificial optoelectronic synaptic devices and show promising potential in emulating human visual perception. In this work, IGZO/WO3−x‐heterostructured artificial optoelectronic synaptic devices are proposed. The device shows a variety of fundamental and advanced electrical and optical synaptic plasticity. By taking advantage of the notable linear synaptic weight changes, ANNs have been constructed and successfully utilized to demonstrate two applications in the field of computer vision, including image segmentation and object tracking.